Fluid balance in youth and adult competitive fencers during simulated competition - Share, B. L.; Edwards, R. B.; Whyte, D. G. (International Journal of Sport Nutrition and Exercise Metabolism, 2022)
Dehydration impairs athletic performance. In addition to its impact on thermoregulation and cardiovascular function, dehydration may also reduce muscular power, cognition and skill execution, all of which are critical attributes in competitive fencing. Fencers require a high level of protective equipment that limits evaporative heat loss, putting athletes at potential risk of dehydration; however, fluid balance during competitive fencing is unknown. Therefore, the purpose of this study was to describe fluid balance in youth and adult fencers during a competitive fencing tournament. Twenty-six fencers (youth, n = 14, 15 ± 2 years; adult, n = 12, 22 ± 5 years) attending a nine-day fencing camp participated in a 3-hour poule competition (WBGT = 18 ± 2°C). Hydration levels at the start of the competition were determined using urine specific gravity (USG) and fluid balance assessed by changes in body weight, corrected for fluid intake and loss. Both youth (1.019 ± 0.010) and adult (1.018 ± 0.009) fencers were hydrated at the start of the tournament (p = 0.84, d = 0.08). Sweat rates in fencers during competition were low (0.22 ± 0.09 L/h) and represented a loss of 1.1 ± 0.4% body mass. Sweat rates (p = 0.85, d = 0.07) and the degree of dehydration (p = 0.45, d = 0.31) was not different between groups. Fencers in both age groups overcompensated for fluid loss, drinking 113 ± 48% of the total volume of sweat lost (p = 0.94, d = 0.03). In conclusion, despite fencers being required to wear a large amount of protective equipment that limits heat loss, sweat rates are low during competitive fencing. Under standard tournament conditions both youth and adult fencers have sufficient opportunity to drink enough to compensate for fluid losses and maintain hydration.